Bone Marrow Transplantation: Pre and after care - Karim, Md Mostafil; Mahfuz, Huque; Uddin, Mohammed Mosleh; Khan, Abul Kashem; Akhter, Shahina (Bangladesh Journal of Medicine, 2023)
Worldwide, Hematopoietic stem cell transplantation is one of the curative options of treatment for hematological malignancies and other hematological diseases. In few recent years, in Bangladesh, Hematopoietic stem cell transplantation (HSCT) has started and improved significantly, especially in patients with hematological malignancies & nonmalignant hematological diseases. As one of the leading BMT Center, CMH Dhaka has started BMT 8 years ago with the successful case of Allogeneic Bone Marrow Transplantation (Allo-HSCT) which was first time in Bangladesh. It was a historic event and landmark achievements in the history of Medical Science of Bangladesh as Allo-HSCT Bone Marrow Transplantation comparatively have a higher risk of life-threatening complications than Auto-HSCT. Till date, Dhaka CMH BMT Center has successfully completed 65 Bone Marrow Transplantation (48 Auto- HSCT & 17 Allo-HSCT). It is an amazing milestone and advancement in medicine of Bangladesh. A series of tests (Like-Hematological profile, Extensive infection screening, Heart function test, Lung function test, Bone Marrow Study, Bone density scan, PET-scan, CT-scan, Chest X-ray, HLA Typing etc.) and procedures can assess general health and the status of patient‘s condition. The tests and procedures also ensure that patient is physically prepared for the transplant. The evaluation may take several days or more. In the days and weeks after bone marrow transplant, BMT specialists do blood tests and other tests to monitor patient‘s condition. They may need medicine to manage complications, such as nausea and diarrhea. After bone marrow transplant, the patient remains under close medical care. If a patient experiencing infections or other complications, he/ she may need to stay in the hospital for several days or longer for close monitoring. Patients may need periodic transfusions of red blood cells and platelets until bone marrow begins producing enough of those cells on its own. Patient needs follow up and Transplant Physician supervision till death. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 191